Impact of Rearing Duration on Nutritional Composition, Flavor Characteristics, and Physical Properties of Asian Swamp Eel (Monopterus albus) - Yuning Zhang; Wentao Xu; Weiwei Lv; Quan Yuan; Hang Yang; Weiwei Huang; Wenzong Zhou (Foods)
The Asian eel, a medicinal and edible species, lacks systematic research on age-related nutritional and flavor dynamics. To optimize breeding strategies and product differentiation, this study systematically investigated the nutritional composition, flavor profiles, and physical properties of Asian eel muscles across five distinct growth stages (1, 3, 7, 11, and 22 years). Results showed that unsaturated fatty acids increased with age, while ω-3/ω-6 ratios peaked in 1-year-old eels. The levels of hydrolyzed essential amino acids were higher in the 3–11-year-old groups, contrasting with higher free amino acids in 1- and 22-year-old eels. Texture declined in hardness/chewiness but improved in resilience with age, linked to muscle fiber density and diameter. One–three-year-old eels exhibited compact muscle fibers and superior texture, while 7–22-year groups demonstrated functional lipid profiles (high docosahexaenoic acid and γ-aminobutyric acid, low cholesterol). These findings highlight age-specific quality traits: 1–3-year-old eels are suitable for fresh consumption, 3–11-year groups offer bioactive benefits, and 22-year-old eels serve as premium functional ingredients. The study provides a scientific basis for targeted breeding and market segmentation to enhance the value of eel aquaculture.